Implementing a Rehabilitation Protocol for Spatial Neglect Assessment and Treatment in an Acute Care Hospital. Issue 2 (April 2020) - Hreha, Kimberly; Chen, Peii; LaRosa, Jennifer; Santos, Christopher; Gocon, Cindy; Barrett, A.M.
Abstract : Purpose: Spatial neglect can occur after stroke, causing disabling spatial errors limiting functional abilities. In rehabilitation research, administration of spatial neglect assessment and treatment protocols can improve function. The objective of this study was to implement those protocols, the Kessler Foundation Neglect Assessment Process (KF-NAP) and the Kessler Foundation Prism Adaptation Treatment (KF-PAT), in an acute care hospital to determine their feasibility and sustainability. Methods: We formally instructed participating therapists, followed by a 5-month training phase and then 6-month implementation phase. Patient participants included right brain stroke survivors, at acute care. We measured patient-based (study participation rates, refusals) and institutional-based feasibility (fidelity and maintenance) for both protocols. Results: A total of 126 of 145 patients with stroke meeting the inclusion criteria were assessed for spatial neglect. Among the 126, 20.6% had spatial neglect. Ten of the 26 patients with spatial neglect were treated with the KF-PAT. There were no refusals; however, 3 people were not seen because of medical scheduling. Overall, the fidelity of both protocols was maintained because main concepts and components were not changed. However, adaptations to both protocols were required secondary to lack of time and medical complexity of the patients. Conclusions: Implementation of a standard rehabilitation assessment and treatment protocol for spatial neglect in acute care is feasible. The findings related to fidelity are promising; however, further research is recommended.